Occurrence of potato pests in different dates of planting in Gangetic plains of West Bengal, India (The Journal of Plant Protection Sciences, 2021)
An experiment on the incidence pattern of various insect pests of potato under five different planting dates (P1 to P5) was  carried out for two consecutive years, 2006-07 and 2007-08 at Adisaptagram Block Seed Farm, Hooghly, West Bengal,  India. Kufri Chandramukhi was planted in five dates of planting starting from 3rd week of November with one week  rd interval upto 3 week of December with a spacing of 60×20 cm. The trial was laid in Randomized Block Design (RBD)  with four replications. The recommended practices for raising the crop in the field was maintained except the application  of insecticides. It was observed that the crops of first planting (at 3rd week of November) harboured less pest infestation.  However, the whitefly infestation was found lower in second and third plantings (at 4thweek of November and 1st week of  December). The infestation of soil pests such as molecricket, cutworm and potato tuber moth were found minimum in  crops of 1st date of sowing resulted in producing highest number of healthy tubers. The rat damage was not so influenced  by different dates of planting. But, the total tuber yield was obtained maximum in second date (4th week of November)  which was closely followed by 1st, 3rd, 4th and 5th dates of sowing.
Keywords: potato; December